Pengaruh Model Brain Based Learning Berbantuan Geogebra Terhadap Kemampuan Pemahaman Konsep Matematis Siswa Ditinjau dari Self-Efficacy - Nasution, Sofyan Husein; Sampoerno, Pinta Deniyanti; Hidajat, Flavia Aurelia (Lattice Journal : Journal of Mathematics Education and Applied, 2025)
This research is motivated by the low ability to understand mathematical concepts of vocational high school students, this is indicated by students still not being able to make mistakes in writing orders in matrices, using the operating rules of matrices, and being less careful in identifying information presented in questions. The purpose of this study is to determine the effect of the brain-based learning model with GeoGebra on students' mathematical concept understanding abilities based on the level of students' self-efficacy. This research method is a quasi-experimental research design with a 2x2 factorial design by level. The research samples taken were students of class XI BR and XI RPL of SMK Negeri 12 North Jakarta, as well as students of class XI TKR and XI TKJ of SMK Negeri 54 Central Jakarta with a total sample of 96 students, divided into 48 experimental classes and 48 control classes, which will be further divided according to the level of self-efficacy possessed by each student. The research instruments used were self-efficacy questionnaire sheets and mathematical context understanding skills test sheets. The data analysis applied in this study includes several tests: Normality Test, Homogeneity Test, effect size test, two-way ANOVA Test, and t-Test. The results of this study are: The ability to understand mathematical concepts of students who are given a brain-based learning model with Geogebra is higher than the conventional learning model, there is an interaction between the learning model and the level of self-efficacy of students; the ability to understand mathematical concepts of students who are given a brain-based learning model is higher than those given a conventional model at a high self-efficacy level; and there is no difference in the ability to understand mathematical concepts between the two models in the low self-efficacy group.. Penelitian ini dilatarbelakangi rendahnya kemampuan pemahaman konsep matematis peserta didik SMK, hal ini ditandai peserta didik masih belum dapat kesalahannya dalam menuliskan ordo pada matriks, penggunaan kaidah operasi dari matriks, serta kurang teliti dalam mengidentifikasi informasi yang dipaparkan dalam soal. Adapun tujuan penelitian ini ialah mengetahui pengaruh model brain based learning dengan geogebra terhadap kemampuan pemahaman konsep matematis peserta didik berdasarkan tingkat self-efficacy peserta didik. Metode penelitian ini ialah quasi eksperimen dengan desain penelitian desain factorial 2x2 by level. Sampel penelitian yang diambil ialah siswa kelas XI BR dan XI RPL SMK Negeri 12 Jakarta Utara, serta siswa kelas XI TKR dan XI TKJ SMK Negeri 54 Jakarta Pusat dengan banyak keseluruhan sampel sebesar 96 peserta didik, yang terbagi atas 48 kelas eksperimen dan 48 kelas kontrol, yang nantinya dibagi lagi sesuai dengan tingkat self-efficacy yang dimiliki setiap peserta didik. Instrumen penelitian yang digunakan ialah lembar angket self-efficacy dan lembar tes keterampilan pemahaman konteks matematika. Analisis data yang diterapkan penelitian ini ialah meliputi beberapa uji: Uji Normalitas, Uji Homogenitas, uji size effect, Uji ANAVA dua arah, dan Uji-t. Hasil dari penelitian ini ialah: Kemampuan pemahaman konsep matematis peserta didik yang diberi model brain based learning dengan geogebra lebih tinggi daripada model pembelajaran konvensional, terdapat interaksi dari model pembelajaran dengan tingkat self-efficacy peserta didik; kemampuan pemahaman konsep matematis peserta didik yang diberi model brain based learning lebih tinggi daripada diberi model konvensional pada tingkat self-efficacy tinggi; serta tidak terdapat perbedaan kemampuan pemahaman konsep matematis antar kedua model pada kelompok self-efficacy rendah.